REALIZATION OF DISCRETE NONLINEAR DYNAMICAL SYSTEMS WITH CHAOTIC REGIMES BASED ON FIXED-POINT ARITHMETIC - U. A. Sychou (Informatika)
In this article, the problem of the practical realization of nonlinear systems with chaotic dynam-ics for targeted generation of chaotic sequences in digital devices is considered. The possible applica-tion in this task with using fixed-point arithmetic to ensure the identity of the obtained results on dif-ferent hardware and software platforms is studied. The implementation of logistic mapping is described; carry out the analysis of the results. This article proposes using the obtained results for the various tasks of the field of mobile robotics.